ФОЙДАЛАНУВЧИНИ ИНДЕНТИФИКАЦИЯЛАШ ВА АУТЕНТИФИКАЦИЯЛАШ ЖАРАЁНЛАРИНИ ТАКОМИЛЛАШТИРИШДА БЛОКЧЕЙН ТЕХНОЛОГИЯСИНИНГ ҚЎЛЛАНИЛИШИ - Рахимбердиев, Қ.Б. (SCIENCE and SOCIETY, 2021)
This article presents ideas for solving user identification and authentication issues, the use of blockchain technology in identification and authentication processes, the essence of using blockchain technology, the effectiveness of using user biometric data in identification and authentication, mathematical model of storing basic biometric data in blocks.
Keywords: identification; authentication; blockchain; block; biometric data; cryptography; encryption; decryption